Media Campaign Management In Head Of Regency/city Election In West Java Province - Mulyana, Slamet (2015)
Head District election is a long awaited democracy festival especially for those who wanted to be in power. Various ways are being done to obtain the position of head district, one of them by employing a campaign. Several campaigns launched by candidates are believed will develop a particular political image for the pair of candidates. One of the campaign components being used is media. The purpose of this research is to gain knowledge on media campaign management by the candidates in Head of District election in West Java Province. Method employed in this research is qualitative descriptive method, and areas of research and informants are purposively being chosen. The area being chosen are Bandung city and Cirebon regency with informants from campaign teams of Ridwan Kamil-Oded M Danial and Budi Dalton-Rizal Firdaus in Bandung, and Hj. Sri Heviyana Supardi-H. Rakhmat in Cirebon. Result of the research outlines the difference of media campaign management patterns in those two areas, which is being adjusted to the area characteristic and voter characteristic. Generally, there is the same understanding about the media campaign management importance by all the campaign teams, including planning stage, implementation stage and evaluation stage. In planning stage, the segmentation of target audience must be definite as the first step to start the decision of how campaign messages are going to be and the selection of media. The combination between conventional media such as newspaper and radio with circulation media and out door media and also new media or convergence media are being implemented. The evaluation of campaign media usage must be done periodically and continuously, especially in an ongoing campaign